Visualization of Understanding Hadith in Animated Cartoon - Hilmy Firdausy (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2021)
Meanwhile, the text is the dominant element used as a medium of delivery in the arena of narration of hadith. The meaning, content and understanding of a hadith are explained in a narrative manner through the arrangement of words and sentences. Instead of clarifying the meaning and understanding of a hadith, the abundance of texts in the writing work actually makes the possibility of the emergence of multiple interpretations even greater. On the other hand, this reality becomes even more counter-productive when it is known that human cognitive work actually relies on “imagery” (al-tasawwur) work. In other words, explaining with pictures is actually more effective than explaining with text. And this kind of momentum is fully held in digital products and content, including animated cartoons. This paper will focus on observing the visualization of hadith understanding in Riko The Series cartoons. Not only explaining how it works, this paper also intends to test the validity of the semantics in the work of the visual narrative.